2021
DOI: 10.20473/jipk.v13i1.19842
|View full text |Cite
|
Sign up to set email alerts
|

Study of Seaweed Kappaphycus alvarezii Explants Growth in the Different Salinity Concentrations

Abstract: HighlightThe best salinity for the thallus growth of K. alvarezii is 32 mg/LThe salinity indicates the osmotic balance of K. alvarezii seaweedThis osmoregulation process affects the nutrient absorption of K. alvarezii seaweedThis study aims to develop the availibility of superior seeds of K. alvareziiAbstract Kappaphycus alvarezii is one of the leading commodities in Indonesian waters. Demand for this commodity is quite high, as reflected in the increasing volume of exports each year. Fulfillment of these dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
5
0
3
Order By: Relevance
“…Salinity is another abiotic factor that may influence the carrageenan yields of K. alvarezii because it affects the seaweed’s osmotic equilibrium and nutrient absorption ( Aris et al, 2021 ). Since carrageenan is essential for maintaining the ionic equilibrium of the cell, it is well recognized that salinity impacts the osmoregulation mechanism, affecting carrageenan yield and quality ( Percival, 1979 ).…”
Section: Factors Affecting Carrageenan Yield and Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity is another abiotic factor that may influence the carrageenan yields of K. alvarezii because it affects the seaweed’s osmotic equilibrium and nutrient absorption ( Aris et al, 2021 ). Since carrageenan is essential for maintaining the ionic equilibrium of the cell, it is well recognized that salinity impacts the osmoregulation mechanism, affecting carrageenan yield and quality ( Percival, 1979 ).…”
Section: Factors Affecting Carrageenan Yield and Productionmentioning
confidence: 99%
“…However, Setyawidati et al (2017) reported that the salinity ranges differing between high (33.8–34.8 psu) and low (33.0–34.0 psu) carrageenan production were only minor, implying that salinity amplitude may be insufficient to explain the variability in carrageenan yield. In contrast, Aris et al (2021) investigated the effect of different salinity levels (30–34 ppt) on the weight of K. alvarezii explants and discovered that the varied salinities affected the growth rate of explants, with the best explant growth occurring at a salinity of 31 ppt and the lowest growth occurring at a salinity of 34 ppt, respectively.…”
Section: Factors Affecting Carrageenan Yield and Productionmentioning
confidence: 99%
“…Suhu pada wadah pemeliharaan rumput laut selama pengukuran yaitu berkisar antara 24-27℃, dimana kisaran suhu tersebut efektif dalam menunjang pertumbuhan serta dapat ditolerir oleh rumput laut. Aris et al (2021) menyatakan, bahwa Eucheuma sp. memiliki suhu toleransi antara 24-36 O C. Suhu berpengaruh dalam proses fisiologi rumput laut, yaitu untuk fotosintesis dan respirasi, serta untuk proses metabolisme sehingga dapat mempengaruhi pertumbuhan rumput laut tersebut (Erwansyah et al, 2021).…”
Section: Hasil Dan Pembahasanunclassified
“…Salinity fluctuated narrowly in the range of 29.4-30.0 ppt which was conducive to K. alvarezii as a stenohaline species (Reis et al, 2011). If seaweed lives at the right salinity, then nutrient absorption and growth at the organ, tissue and cell levels will run well (Lobban &Harrison, 2000 andAris et al, 2021). In addition to the ability of seaweed to produce oxygen through photosynthesis, the aeration factor in this study contributed to the dissolved oxygen (Kumar et al, 2013), which was in the range of 5.3-7.5 mg L -1 .…”
Section: Water Quality Parametersmentioning
confidence: 99%